Analysis Consumer Purchasing Decisions in the App Tokopedia Through E-Wom, Experiental Marketing and Brand Ambassador - Agustini Tanjung; Hermiyetti; Usmar; Primaraga Sumantri Indra Wicaksana (Institute of Computer Science (IOCS), 2022)
The purpose of this study was to examine the effect of electronic word of mouth, experiential marketing, and brand ambassador variables on purchasing decisions on the Tokopedia application in the West Cikarang region. This sampling technique uses the Lemeshow formula and obtained as many as 300 respondents. The data obtained were analyzed quantitatively by using measuring instruments in the form of validity tests, reliability tests, classical assumption tests, simple and multiple linear regression analysis tests, and hypothesis testing. The test was conducted to determine the effective and relative contribution by using the SPSS version 21 application program for windows. The results of partial statistical analysis show that electronic word of mouth, experiential marketing, and brand ambassadors have a positive and significant influence on purchasing decisions on the Tokopedia application. The results of statistical analysis simultaneously show that electronic word of mouth, experiential marketing, and brand ambassadors have a significant effect on purchasing decisions on the Tokopedia application simultaneously. The results of the R Square value of electronic word of mouth showed a value of 48.4%, experiential marketing showed a value of 67.0%, and brand ambassadors showed a value of 66.0% which means that there is an influence on purchasing decisions on the Tokopedia application in the West Cikarang region.